UNDERSTANDING ACCOUNTING IN SUPPORTING REPORTS QUALITY FINANCE AT PT. PASANGGRAHAN CITRA PERSADA: PEMAHAMAN AKUNTANSI DALAM MENDUKUNG LAPORAN KEUANGAN BERKUALITAS PADA PT. PASANGGRAHAN CITRA PERSADA - Yunita Kurnia Shanti; Susi Sih Kusumawardhany; Sudarmadi Sudarmadi (ASOSIASI IDEBAHASA KEPRI, 2023)
Financial statements are a form of accountability for the management of economic resources owned by an entity. Published financial reports must be prepared in accordance with applicable accounting standards so that these financial statements can be compared with the financial statements of the previous period or compared with the financial statements of a clear entity. Quality of financial reports - (financial statement) is the final result of the process of accounting activities or a summary of financial transactions. Financial statements are prepared to provide information about the position of assets, debts and capital that occur in the company's household as well as its profits and losses. The characteristics of financial reports in terms of quality are based on the Accounting Standards Guide (PSAK), namely: Understandability, Relevance, Materiality, Reliability, Honest presentation, Substance over form, Neutrality, Fair consideration and Completeness. Based on the problems mentioned above, we conducted community service at PT Pasanggrahan Citra Persada, which is an l‹loantral‹tor company engaged in structural work, architects and interiors, with an expert and skilled workforce. PT Pasanggrahan Citra Persada emphasizes sustainable company growth to become one of the best quality construction companies in Indonesia with competency development through human resource development, technology management and good corporate governance.